Effect of Blended Nitrogen, Phosphorus, Sulfur, Boron, and Potassium Fertilizer Rates on Growth and Yield of Maize (Zea mays L.) at Sodo Zuriya District, Southern Ethiopia - Gobeze Loha; Melese Derese; Gidago Gifole (Applied and Environmental Soil Science)
There are various challenges that limit crop productivity in developing countries like Ethiopia. Lack of accessible plant nutrients in proper quantity as well as form to plants is an important determinant of reducing agricultural productivity. In this regard, a trial was conducted at Shela Borkoshe on the land owned by the farmer in Sodo Zuriya District, Wolaita Zone, Southern Ethiopia over the planting seasons of 2019 to 2020 with the aim of identifying the appropriate rates of blended nitrogen, phosphorus, sulfur, boron (NPSB), and potassium (K) fertilizer in maize production. The treatments, which were assessed using a factorial randomized complete block design with three replications, comprised of four rates of blended NPSB (0, 50, 100, and 150 kilograms/hectare) and four rates of K (0, 30, 60, and 90 kilograms/hectare K2O). Agronomic traits leaf area, LAI, ear length, seeds per row, seeds per ear, TSW, biomass as well as grain produce have been significantly varied due to NPSB by K fertilizer rates interactions. The highest leaf area (9886.20 ± 343.95 cm2), LAI (7.78 ± 0.26), ear length (32.58 ± 1.46 cm), TSW (160.67 ± 4.85 g), biomass (14941 ± 200.92 kilograms/ha), and grain output (7544 ± 119.49 kilograms/ha) have been attained by combining 150 kilograms/ha NPSB and 90 kilograms/ha K fertilizer rate. Following this, maximum quantity of seeds per row (44.88 ± 1.67) and seeds per ear (705.87 ± 25.61) have been attained from combination of 150 kilograms/ha NPSB and 60 kilograms/ha K fertilizer rates. Economic analysis revealed that maximum net profit (1491 Dollar/ha) and marginal rate of return (MRR) 1196.67% have been achieved from combining 150 kilograms/ha NPSB and 60 kilograms/ha K fertilizer rates. This investigation revealed that the combination of the NPSB fertilizer level of 150 kilograms/ha and 60 kilograms/ha K fertilizer showed superior performance with higher grain yield and economic return over other treatments. Therefore, a combined application of 150 kilograms/ha NPSB with 60 kilograms/ha K fertilizer rates could be recommended for maize production in the study area and similar agro-ecologies.